ANALISIS FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR TRANSPORTASI & LOGISTIK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Gregorius Gorang (2022)
This quantitative research aims to examine and determine the effect of profitability, liquidity and firm size on financial distress. The population used is the transportation and logistics sector companies listed on the Indonesia Stock Exchange (IDX) in the 2018-2020 period. probability sampling was used as a sampling technique in this study in order to obtain 27 companies in the transportation and logistics sector. The data in this study is secondary data and analyzed using logistic regression method and tested using partial significance test (Z test) and Mc Fadden test (R2). The results of this study indicate that liquidity has an effect on financial distress, while profitability and firm size have no effect on financial distress.